OPENING THE EYES ABOUT DICTATORSHIP: AUDIO DESCRIPTION AS A RESOURCE OF BRAZILIAN MEMORY 'S MAINTENANCE - Villela, Lucinea Marcelino [UNESP]; Losnak, Celio Jose [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2016)
In 2014 the Brazilian society had the opportunity to debate the harsh period of its dictatorship after 50 years since the 1964 Military Coup. The main goal of this paper is the presentation of an Audio Description project with remarkable photos and videos from Brazilian Dictatorship and its reflections on Brazilian society. The project was elaborated by the research group Accessible Media and Audiovisual Translation, whose main focus is provide accessibility (audio description and subtitles) for different audiovisual products. We produced a photo documentary with an overview of some important images and with a script focusing on important information about Brazilian politics from 1964 up to 1989. Many steps were followed during the whole process:selection of photos, historical contextualization, script, narration, final editing of the video. In order to produce the audio description scripts of photos and images selected, we have followed some assumptions about audio description. According to Matamala (2006:330) various competences are required to audio describers such as:the ability to undertake intersemiotic translations (turning images into words), the ability to summarise information in order to adapt the text to the limited space available, keeping the original meaning, by means of rewording and by using synonyms; the ability to critically select the most relevant information.
Keywords: Accessibility; Audiovisual Translation; Audio description; Brazilian Dictatorship